PERTUMBUHAN BIBIT KARET (Hevea brasiliensis L.) ASAL OKULASI PEMBERIAN BOKASHI DAN PUPUK ORGANIK CAIR BINTANG KUDA LAUT - Purwati MS (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2013)
The experiment aimed to identify the growing of rubber seedling (Hevea brasilliensis L.) from oculation upon the application of Bokashi and Bintang Kuda Laut organic liquid fertilizer, as well as its interaction, and to find the proper dosage of Bokashi and Bintang Kuda Laut organic liquid fertilizer for rubber seedling. The experiment lasted for four months, from June to September 2012, at the screen house Agriculture Faculty Widya Gama Mahakam University, Sempaja Samarinda city. The experiment employed Completely Randomized Design with factorial 3x4 and three replications. The first factor was Bikashi (B): no bikashi (b0); 300 g bokashi/polybag (b1); 600 g bokashi/polybag (b2). And the secand factor was Bintang Kuda Laut Organic liquid fertilizer (P): no organic liquid fertilizer (p0); 3 ml/liter water (p1); 6 ml/liter water (p2); and 9 ml/liter water (p3). Results of the experiment showed that: (1) significant responses of Bokashi on the parameters of plant height, number of leaf at the stage of 60 and 90 old days after planting and diameter of stem; (2) significant responses on the application of Bintang Kuda Laut Organic liquid fertilizer on plant height, number of leaf at the stage of 60 and 90 old days and diameter of stem; (3) there was no significant responses on all parameters upon the interaction between bikashi and Bintang Kuda Laut organic liquid fertilizer application.